2010
DOI: 10.1096/fj.09-144659
|View full text |Cite
|
Sign up to set email alerts
|

Granulin epithelin precursor: a bone morphogenic protein 2‐inducible growth factor that activates Erk1/2 signaling and JunB transcription factor in chondrogenesis

Abstract: Granulin epithelin precursor (GEP) has been implicated in development, tissue regeneration, tumorigenesis, and inflammation. Herein we report that GEP stimulates chondrocyte differentiation from mesenchymal stem cells in vitro and endochondral ossification ex vivo, and GEP-knockdown mice display skeleton defects. Similar to bone morphogenic protein (BMP) 2, application of the recombinant GEP accelerates rabbit cartilage repair in vivo. GEP is a key downstream molecule of BMP2, and it is required for BMP2-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
162
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(168 citation statements)
references
References 70 publications
6
162
0
Order By: Relevance
“…Based on the findings in this study, together with the literature (Ron and Walter, 2007;Murakami et al, 2009;Han et al, 2014;Cantu' et al, 2011;Roca et al, 2005;Kronenberg, 2006;Yamamoto et al, 2004), as well as our previous reports (Guo et al, 2014b;Han et al,2014;Feng et al, 2010), we propose a model for illustrating the role and regulation of ATF6a in the course of hypertrophic chondrocyte differentiation (Fig. 8I).…”
Section: There Are Three Runx2-binding Consensus Sequences [Rccrc(a/tsupporting
confidence: 82%
See 1 more Smart Citation
“…Based on the findings in this study, together with the literature (Ron and Walter, 2007;Murakami et al, 2009;Han et al, 2014;Cantu' et al, 2011;Roca et al, 2005;Kronenberg, 2006;Yamamoto et al, 2004), as well as our previous reports (Guo et al, 2014b;Han et al,2014;Feng et al, 2010), we propose a model for illustrating the role and regulation of ATF6a in the course of hypertrophic chondrocyte differentiation (Fig. 8I).…”
Section: There Are Three Runx2-binding Consensus Sequences [Rccrc(a/tsupporting
confidence: 82%
“…5. For Safranin O and Fast Green staining, and Alizarin Red or Alcian Blue staining, the methods were as explained previously (Feng et al, 2010;Guo et al, 2014a,b).…”
Section: Fetal Mouse Bone Explants Culturementioning
confidence: 99%
“…PGRN is a 66-68 kDa secreted glycoprotein, also known as proepithelin cell-derived growth factor (PCDGF), has been shown to be a pluripotent growth factor that plays a role in cell-cycle progression, angiogenesis, wound healing, cancers, and neurodegenerative diseases (He and Bateman, 2003;Feng et al, 2010).…”
Section: Progranulin (Pgrn)mentioning
confidence: 99%
“…However, previous evidences suggested that endoplasmic reticulum (ER) stress may be involved in PGRN action in some other pathological processes. For instance, PGRN activates ERK1/2 signaling pathway, 16 whereas XBP1S, a key transcription factor in ER stress, inhibits ER stress-mediated apoptosis through the Erk1/2 signaling pathway. 17 In addition, tumor necrosis factor-a (TNFa), a putative inducer of inflammation, ER stress and insulin resistance, [18][19][20][21][22] significantly augments PGRN expression in 3T3-L1 adipocytes.…”
Section: Introductionmentioning
confidence: 99%